2013
DOI: 10.1080/00028487.2013.763858
|View full text |Cite
|
Sign up to set email alerts
|

Movements by Adfluvial Bull Trout during the Spawning Season between Lake and River Habitats

Abstract: Movements of adfluvial Bull Trout Salvelinus confluentus were evaluated with acoustic telemetry during spawning seasons 2006–2011 in Chester Morse Lake,Washington. Ninety‐six percent of the individuals made multiple trips between the lake and river habitat during the spawning season,which lasted from less than 1 day to more than a month. Male Bull Trout took an average 13.2 (± 8.7 SD) trips,while females averaged 18.0 (± 14.0 SD) trips. Directional movement between the lake and a river occurred throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…America also exhibit a variety of spawning movement patterns including adfluvial (i.e., lake rearing and stream spawning; Cope 1956;Downs et al 2006;Holecek and Walters 2007;Barnett and Paige 2013), fluvial (i.e., larger spawning and rearing movements within streams; Colyer et al 2005;AlChokhachy and Budy 2008;Pierce et al 2009), and tributary residency (Young 1995), and multiple movement patterns are often demonstrated within a single watershed (Al-Chokhachy and Budy 2008). The diversity of potamodromous trout spawning movements is thought to be part of a complex set of life history characteristics that have evolved in response to frequent changes in the spatial and temporal availability of suitable habitat (Gresswell et al 1994;Northcote 1997;Dunham et al 2003).…”
Section: ) Potamodromous Trout Populations Of Western Northmentioning
confidence: 99%
“…America also exhibit a variety of spawning movement patterns including adfluvial (i.e., lake rearing and stream spawning; Cope 1956;Downs et al 2006;Holecek and Walters 2007;Barnett and Paige 2013), fluvial (i.e., larger spawning and rearing movements within streams; Colyer et al 2005;AlChokhachy and Budy 2008;Pierce et al 2009), and tributary residency (Young 1995), and multiple movement patterns are often demonstrated within a single watershed (Al-Chokhachy and Budy 2008). The diversity of potamodromous trout spawning movements is thought to be part of a complex set of life history characteristics that have evolved in response to frequent changes in the spatial and temporal availability of suitable habitat (Gresswell et al 1994;Northcote 1997;Dunham et al 2003).…”
Section: ) Potamodromous Trout Populations Of Western Northmentioning
confidence: 99%
“…The observed concentration of redds at this distance in all study years probably correlates with the diversity and quantity of habitat available to Bull Trout. Finally, we have documented tagged Bull Trout that make multiple trips between CML and river habitat during a single spawning season (Barnett and Paige 2013). Such behavior during the spawning season may increase the likelihood of Bull Trout spawning immediately upstream of the reservoir because the fish seek spawning habitat and partners while making relatively short, multiple movements between the river and reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, individuals move between stream systems within a single year, increasing the possibility of spreading spawning events spatially and temporally. By taking multiple trips into the river system (and potentially spawning with more than one partner), temporal and spatial variability of spawning is increased in the population (Barnett and Paige 2013). These behavioral characteristics interplay with environmental variables (e.g., streamflow, temperature, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Given the species' sensitivity to water temperature (Selong et al 2001), bull trout were predicted to have the smallest home ranges during the warmest and coldest periods of the year, i.e., summer and winter. Reproductive migrations and their preference for cool water were expected to result in large home ranges and greater total monthly displacement in the fall months (Barnett and Paige 2013). Given that egg development is energetically costly compared with the cost of producing sperm and a larger body size requires more energy intake Fausch 1996, Wootton 1998), I predicted large females would possess the largest home range sizes and perform the greatest horizontal movement over the study period.…”
Section: Introductionmentioning
confidence: 99%
“…Taken collectively, the movement of many individuals can illustrate generalized patterns for whole aggregations, populations, communities, and meta-communities (Turchin 1998; Giuggioli and Bartumeus 2010; Morales et al 2010). As such, organism movement is useful to test hypotheses about animal behaviour (Downes 2001;Busch and Mehner 2012), describe ecology (Bahr and Shrimpton 2004;Pade et al 2009), and to direct management and conservation activities (Marshell et al 2011;Barnett et al 2013). In a recent review, Holyoak et al (2008) found that an average of approximately 2 600 peer-reviewed articles/year were published on organism movement between 1997 and 2006.…”
mentioning
confidence: 99%